2019
DOI: 10.1111/hsc.12895
|View full text |Cite
|
Sign up to set email alerts
|

“Caregiving is a full‐time job” impacting stroke caregivers' health and well‐being: A qualitative meta‐synthesis

Abstract: Family caregivers contribute to the sustainability of healthcare systems. Stroke is a leading cause of adult disability and many people with stroke rely on caregiver support to return home and remain in the community. Research has demonstrated the importance of caregivers, but suggests that caregiving can have adverse consequences. Despite the body of qualitative stroke literature, there is little clarity about how to incorporate these findings into clinical practice. This review aimed to characterise stroke c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 79 publications
(217 reference statements)
8
75
0
2
Order By: Relevance
“…Focusing on social support, the score for the sub‐dimension social dysfunction in perceived health is high, which means that the caregivers’ perception of emotional well‐being has been affected, as discussed in other studies (Campos‐Puente et al., 2019; Kokorelias et al., 2020). Nonetheless, the score for perceived social support is high.…”
Section: Discussionmentioning
confidence: 62%
“…Focusing on social support, the score for the sub‐dimension social dysfunction in perceived health is high, which means that the caregivers’ perception of emotional well‐being has been affected, as discussed in other studies (Campos‐Puente et al., 2019; Kokorelias et al., 2020). Nonetheless, the score for perceived social support is high.…”
Section: Discussionmentioning
confidence: 62%
“…Stroke patients who are divorced or whose spouses need to go out to work to make a living need to be cared for by their living parents. The physical and mental health and living status of caregivers determine the quality of life and prognosis of patients, but studies pay more attention to elderly stroke patients and their spouses, and there are few reports from other caregivers 40–42 . Recent studies showed that caregiving burden was predominantly shouldered by female caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…The physical and mental health and living status of caregivers determine the quality of life and prognosis of patients, but studies pay more attention to elderly stroke patients and their spouses, and there are few reports from other caregivers. [40][41][42] Recent studies showed that caregiving burden was predominantly shouldered by female caregivers. Caregivers faced physical, psychological, and socioeconomic burden.…”
Section: Hospitalization Process Informationmentioning
confidence: 99%
“…17 The CASP is a commonly used tool in appraising the quality of qualitative research, 18 and has been used previously in qualitative stroke research. 19,20 This 10-item checklist assesses three domains: validity, results and relevance to practice. All reviewers met to orientate themselves to the CASP tool, it’s rules and instructions prior to commencing quality assessment to ensure consistency and accuracy of use.…”
Section: Methodsmentioning
confidence: 99%